Dampak Amnesti Pajak dan Sistem Administrasi Modern terhadap Kepatuhan Wajib Pajak - Sri Risma Yenny; Pulung Wicaksono (Politeknik Negeri Lampung, 2019)
The purpose of this study is to find empirical evidence of the impact of tax amnesty and the modern administration system on taxpayer compliance on individual taxpayers in Lampung Province. The object chosen is the taxpayers having NPWP in Lampung Province. The data used are primary data obtained by distributing questionnaires to respondents and processed with Likert scale. The samples in this study were 114 people taken randomly. This research is a quantitative research with warpPLS 3.0 test equipment to process data obtained from questionnaires. The results of the study show that tax amnesty as well as the modern administration system has a significant effect on taxpayer compliance.